Förvildade husdjur : möjligheter och hot - Noréus, Stina (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2012)
Feral animal populations are distributed over many parts of the world and are often seen as a problem. Since they are a threat against other species, destroy farmlands and can spread dis-eases, they are often referred to as pests. Artificial selection has contributed to loss of genetic diversity in our domesticated animals. Feral animal populations are affected by natural selec-tion, which allows them to adapt to the environment. Their ability to adapt is a reason to see them as pests but can also be seen as an asset. The purpose of this paper was to study the posi-tive aspects of feral animal populations and how they can be used in animal science. Rapid environmental changes in the future can make them an important genetic resource. Unique alleles have e.g. been found in semi-feral cattle populations. Behavioral studies can provide important knowledge about domestic animals that their wild ancestors cannot. Population genetic studies can provide insight in genetic structure, population structure and distribution patterns that can be used to setup control strategies both for conservation of wild populations and management of feral animal populations. Feral animal populations should be seen as a potentially important genetic resource but it is also important to take the surrounding envi-ronment in to account.